Preponderant clonal evolution of Trypanosoma cruzi I from Argentinean Chaco revealed by Multilocus Sequence Typing (MLST) - Tomasini, Nicolás (2014)
Trypanosoma cruzi has been historically classified as a species with preponderant clonal evolution (PCE). However, with the advent of highly polymorphic markers and studies at geographically reduced scales,the PCE in T. cruzi was challenged. In fact, some studies have suggested that recombination in T. cruzi lineage I (TcI) is much more frequent than previously believed. Further analyses of TcI populations from different geographical regions of Latin America are needed to examine this hypothesis. In the present study,we contribute to this topic by analyzing the population structure of TcI from a restricted geographical area in the Chaco region, Argentina. We analyzed TcI isolates from different hosts and vectors using a Multilocus Sequence Typing (MLST) approach. These isolates were previously characterized by sequencing the spliced leader intergenic region (SL-IR). Low levels of incongruence and well-supported clusters for MLST dataset were obtained from the analyses. Moreover, high linkage disequilibrium was found and five repeated and overrepresented genotypes were detected. In addition, a good correspondence between SL-IR and MLST was observed which is expected under PCE. However, recombination is not ruled out because five out of 28 pairs of loci were incompatible with strict clonality and one possible genetic exchange event was detected. Overall, our results represent evidence of PCE in TcI from the study area.Finally, considering our findings we discuss the scenario for the genetic structure of TcI.